2010
DOI: 10.1152/ajpheart.00727.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced in vivo high-energy phosphates precede Adriamycin-induced cardiac dysfunction

Abstract: is an established, life-saving antineoplastic agent, the use of which is often limited by cardiotoxicity. ADR-induced cardiomyopathy is often accompanied by depressed myocardial high-energy phosphate (HEP) metabolism. Impaired HEP metabolism has been suggested as a potential mechanism of ADR cardiomyopathy, in which case the bioenergetic decline should precede left ventricular (LV) dysfunction. We tested the hypothesis that murine cardiac energetics decrease before LV dysfunction following ADR (5 mg/kg ip, wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Studies performed in humans and animal models of cardiac failure demonstrate that a decrease in Cr levels antedates a decrease in ATP levels, the latter which is a hallmark of advanced cardiac failure (Maslov et al 2010;Neubauer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in humans and animal models of cardiac failure demonstrate that a decrease in Cr levels antedates a decrease in ATP levels, the latter which is a hallmark of advanced cardiac failure (Maslov et al 2010;Neubauer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DOX also inhibits the creatine kinase (CK) reaction, the prime myocardial energy reserve reaction which rapidly and reversibly exchanges a phosphoryl group between ATP and PCr [23-26]. Following chronic DOX administration in a murine model, myocardial energetic changes, indexed by a reduced PCr/ATP ratio, occur relatively early and precede the appearance of contractile dysfunction and predict the subsequent degree of contractile abnormalities [27], suggesting, but not proving, a causal role for impaired energy metabolism in subsequent DOX-induced cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Even though several pathways such as mammalian target of rapamycin inhibition (Zhu et al, 2009), phosphodiesterase-5 inhibition (Fisher et al, 2005), reduction in circulating progenitor cells (Huang et al, 2010), activation of Toll-like receptors (Nozaki et al, 2004;Riad et al, 2008), impaired metabolism (Maslov et al, 2010), and triggering autophagy (Kobayashi et al, 2010) have been identified, the precise mechanism of Dox-induced cardiotoxicity still remains unclear. We recently identified a novel pathway: that heat shock factor (HSF-1) is activated because of Dox-induced oxidative stress, and this activation enhanced the expression of heat shock proteins including Hsp25 in Dox-treated mouse hearts (Vedam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%